PENGARUH KESADRAN WAJIB PAJAK, PEMAHAMAN PAJAK DAN SANKSI PERPAJAKAN TERHADAP KEPATUHAN WAJIB PAJAK DI KPP PRATAMA BATAM SELATAN - Ritonga, Irma Sri Lestari; Poniman (SCIENTIA JOURNAL, 2022)
The purpose of this study is to identify how much influence taxpayer awareness, tax understanding and tax sanctions have on taxpayer compliance at KPP Pratama Batam Selatan. This data collection was carried out using a questionnaire which was measured using a Likert scale. The population taken in this study are individual taxpayers who have been registered at the KPP Pratama Batam Selatan, totaling 346,849 people and the sampling technique is carried out using the slovin formula calculation, from the slovin formula calculation, the sample in this study is 100 people taxpayer respondents. personal. The data analysis method used in this study is quantitative data analysis with data collection techniques, namely descriptive analysis, validity test, reliability test, multiple linear regression test, normality test, multicollinearity test, heteroscedasticity test, F test, T test and determination test. . The data is processed using SPSS 25. The results show that taxpayer awareness affects taxpayer compliance, tax understanding affects taxpayer compliance, tax sanctions have no effect on taxpayer compliance and together taxpayer awareness, tax understanding and tax sanctions affect taxpayer compliance. taxpayer compliance at KPP Pratama South Batam. Keywoards : Taxpayer Compliance; Taxpayer Awareness; Tax Understanding; Tax Sanctions